Asthma Guideline Barriers in Primary Care - Luqyaanaa Rihaadatul 'Aisy; Alfian Nur Rosyid (Universitas Airlangga, 2026)
Asthma continues to be a global health concern, with significant prevalence and mortality rates worldwide. In Indonesia, the asthma prevalence is 2.4%, and it is a leading cause of death, with an expected increase in the next decade if not effectively managed. National and international guidelines, such as those from the Global Initiative for Asthma (GINA), are crucial in improving asthma management. However, physician adherence to these guidelines remains a challenge, particularly in primary care settings. This literature review aims to identify the major barriers to implementing asthma management guidelines among general practitioners in primary care settings, including insufficient access to diagnostic tools and medications, inadequate physician knowledge, insurance reimbursement constraints, time and workforce limitations, and the complexity of GINA guidelines. Studies in various countries, including Nigeria, Malaysia, and Yemen, highlight these barriers and their impact on the quality of asthma care. Addressing these issues through improved resource availability, enhanced physician training, and the adaptation of guidelines to local contexts is essential for improving asthma management and patient outcomes, particularly in developing countries. Overcoming these barriers can also help reduce healthcare costs associated with asthma management.